Ancient texts, papyri, and manuscripts studies in honor of James R. Royse - Royse, James Ronald 1944-; Farnes, Alan Taylor 1985-; Mackie, Scott D. 1964-; Runia, David T. 1951- (Boston BRILL, 2021)
This volume honors Prof. James R. Royse for his scholarly achievement in the fields of New Testament textual criticism and Philonic studies. It contains seventeen articles, prefaced by an introductory biographical article and a list of his publications.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Festschrift; Aufsatzsammlung